Bułgarskie przekłady bajek Ezopa i ich rola w kształtowaniu odrodzonego społeczeństwa w XIX wieku - Walczak-Mikołajczakowa, Mariola (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The article considers the Bulgarian translations of Aesop’s fairy tales done in the nineteenth century. Then they occupied an important place in the textbooks for the newly emerging secular schools. As a popular reading, they also played an important role in the discussion on normalization of the Bulgarian language.